2020
DOI: 10.3390/genes11121431
|View full text |Cite
|
Sign up to set email alerts
|

PupStruct: Prediction of Pupylated Lysine Residues Using Structural Properties of Amino Acids

Abstract: Post-translational modification (PTM) is a critical biological reaction which adds to the diversification of the proteome. With numerous known modifications being studied, pupylation has gained focus in the scientific community due to its significant role in regulating biological processes. The traditional experimental practice to detect pupylation sites proved to be expensive and requires a lot of time and resources. Thus, there have been many computational predictors developed to challenge this issue. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Attempts have been made to identify a substrate recognition pattern for PafA through bioinformatic analysis of the pupylome data sets. However, the results have been inconclusive 25 27 . In proteomics experiments for the identification of modified proteins, a common approach is to include an enrichment step during purification to separate the modified from unmodified proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made to identify a substrate recognition pattern for PafA through bioinformatic analysis of the pupylome data sets. However, the results have been inconclusive 25 27 . In proteomics experiments for the identification of modified proteins, a common approach is to include an enrichment step during purification to separate the modified from unmodified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified hundreds of putative pupylation substrates, spanning proteins from diverse functional classes without a clear preference. Bioinformatic analysis of these pupylomes has revealed statistical differences in amino acid frequencies in the sequence neighborhood of target lysine residues compared to non-target lysines 25 27 . However, these patterns are insufficient to predict experimentally validated target lysines.…”
Section: Introductionmentioning
confidence: 99%
“…To know the molecular mechanisms of pupylation, it is necessary to define the substrates of pupylation and its sites precisely. Typically, this task is labor-intensive and time-consuming because of the large-scale analysis of proteomics; thus, a few computational methods of predicting pupylation sites have been proposed [ 12 , 13 , 14 , 15 , 16 ]. Liu et al first developed the GPS-PUP predictor for the prediction of pupylation sites by the group-based prediction system (GPS) method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%